History of Urology at the Sestre Milosrdnice University Hospital Center - Boris Ružić; Josip Katušić; Borislav Spajić; Ante Reljić; Alek Popović; Goran Štimac; Igor Tomašković; Šoip Šoipi; Danijel Justinić; Igor Grubišić; Miroslav Tomić; Matej Knežević; et al. (Acta Clinica Croatica, 2018)
The history of Croatian urology clearly shows its affiliation to the medical and civilizational circle of the Western world. The Department of Urology at the Sestre milosrdnice University Hospital Center is the oldest urology institution in the Republic of Croatia. The Department was established in 1894, when the new Sestre milosrdnice Hospital was open in Vinogradska cesta in Zagreb. It was then that doctor Dragutin Mašek founded the so-called III Department, which, in addition to treating urology patients, also treated patients with conditions of the ear, nose and throat, eye diseases and dermatologic conditions. Dragutin Mašek had already realized that medicine would soon be divided into fields and had assigned younger doctors joining the III Department to specific fields. As a result, urology was given to Aleksandar Blašković, who founded the first independent department of urology in Croatia in 1926. In 1927, he was appointed Professor of urology at the Zagreb School of Medicine, where he established the first department of urology and was giving lectures and practicals. Under his leadership, the Department of Urology was given the status of a Clinic, a teaching department, the first of its kind in Croatia. Owing to all his activities in the field of urology, the history remembers him as the “father of modern Croatian urology”. Over the course of the following years, department chairs had changed, but luckily for the patients, approach to work had not. Conscientiousness, trust, competence and charity. After all, charity is the idea that the hospital carries even in its name, after the Sisters of Charity who had founded it. In all the decades, the Department of Urology has been following global development paths, objectively legging behind top facilities in the world by only a few years. Overall professional and scientific urology activities culminated in 1998, when the Clinic became the Reference Center of the Ministry of Health of the Republic of Croatia for prostate cancer, and in 2011, when it became the European Board of Urology Certified Center. All that has been achieved could not have been done without wholehearted help and cooperation of the nurses, as well as every other department employee from the beginnings of urology until today. Despite its rich history, the Department does not rest on laurels. Today, it is a modern urology department together with its European role models.